P223 Understanding the greater burden of STIS among black caribbeans in the UK: evidence from a systematic review. (18th May 2015) - Wayal, Sonali; Griffiths, Catherine; Mercer, Catherine; Gerressu, Makeda; Hughes, Gwenda
Abstract : Background: In the UK, Black Caribbeans are disproportionately affected by STIs. Aim: We conducted a systematic review of attitudinal, behavioural and contextual risk factors of this inequality. Methods: Ten electronic databases were searched for studies on risk factors and drivers of STI among UK Black Caribbeans from 1948 to 30/11/2014. Two independent reviewers screened all identified abstracts and extracted data from selected studies using standardised forms. Results: Of 3220 abstracts identified, 165 were included in the review. STI risk among Black Caribbeans is higher compared to other ethnic groups and varies by gender and age. Being single and reporting first intercourse aged <16, >1 new sex partner in the past year, concurrency, and assortative sexual mixing were identified as risk factors. STIs were considered of lower priority than HIV/unplanned pregnancy. Barriers to condom use, especially among women with older and regular partners, were reported. Compared to other ethnic groups, Black Caribbeans were more likely to have ever attended a STI clinic and tested for HIV, but Black Caribbean women were more likely to report delays in seeking care and be sexually active whilst symptomatic. Perceived negative attitudes of clinic staff of the same ethnicity towards young women negatively affected care-seeking. Discussion/conclusion: Sexual behavioural risk factors or access to care did not fully explain the disproportionate STIs burden among Black Caribbeans highlighting the need for further evidence on contextual drivers of STIs. STI reduction interventions should be gender-specific, informed by partnership patterns and address attitudes to STIs and sexual health care-seeking.